Breastfeeding the preterm infant - Luigi Corvaglia; Silvia Martini; Giacomo Faldella (Hygeia Press di Corridori Marinella, 2013)
Due to its peculiar nutritional and non-nutritional contents, which include long-chain polyunsatured fatty acids (LC-PUFA), prebiotics, immunological factors, hormones and growth factors, breast milk shows significant advantages over infant formulas in nourishing preterm infants. Better neurocognitive outcomes, which are reported to persist far beyond the early childhood, have been largely observed in breastfed preterm infants; a role of LC-PUFA in promoting neural and retinal development is assumed. As far as the gastrointestinal tract is concerned, several evidences have reported a dose-related reduction in NEC incidence among preterm infants fed on human milk. Moreover, the higher amount of immunological factors as secretory IgA within preterm breast milk might play a remarkable role in reducing the overall infections. Despite breastfeeding in preterm infants is generally linked with lowered growth rates which might potentially affect neurocognitive outcomes, the beneficial effects of human milk on neurodevelopment prevail. Fortified human milk might better fulfill the particular nutritional needs of preterm infants. However, as breast milk fortification is difficult to carry out after the achievement of full oral feeding, some concerns on the nutritional adequacy of exclusive breastfeeding during hospitalization as well as after discharge have been raised. Finally, breastfeeding also entails maternal psychological beneficial effects, as promoting the motherhood process and the mother-child relationship, which could be undermined in those women experiencing preterm delivery.   Proceedings of the 9th International Workshop on Neonatology · Cagliari (Italy) · October 23rd-26th, 2013 · Learned lessons, changing practice and cutting-edge research